The design of a human memory prosthesis - Sellen, Abigail (Computer Journal, 1994)
Memory is the forgotten problem of office systems research. We believe that a new class of applications, which we call “memory prostheses”, are needed when memory problems arise. We expect these systems to provide help with a range of everyday memory problems, including: finding files, papers and notes (in whatever medium they are expressed), recalling names of people and places, procedures and lists, remembering to perform tasks. A memory prosthesis will be sensitive to its environment and able to record data automatically about its user’s activities. These data can later be retrieved to help users remember things they have forgotten, especially things they did not know they would need to remember. This sensitivity to the environment will also enable the memory prosthesis to issue context-sensitive reminders of things that the user intended to do